Endoplasmic reticulum dysfunction in neurological disease - Roussel, Benoit D; Kruppa, Antonina J; Miranda, Elena; Crowther, Damian C; Lomas, David A; Marciniak, Stefan J (Lancet neurology, 2013)
Endoplasmic reticulum (ER) dysfunction might have an important part to play in a range of neurological disorders, including cerebral ischaemia, sleep apnoea, Alzheimer's disease, multiple sclerosis, amyotrophic lateral sclerosis, the prion diseases, and familial encephalopathy with neuroserpin inclusion bodies. Protein misfolding in the ER initiates the well studied unfolded protein response in energy-starved neurons during stroke, which is relevant to the toxic effects of reperfusion. The toxic peptide amyloid β induces ER stress in Alzheimer's disease, which leads to activation of similar pathways, whereas the accumulation of polymeric neuroserpin in the neuronal ER triggers a poorly understood ER-overload response. In other neurological disorders, such as Parkinson's and Huntington's diseases, ER dysfunction is well recognised but the mechanisms by which it contributes to pathogenesis remain unclear. By targeting components of these signalling responses, amelioration of their toxic effects and so the treatment of a range of neurodegenerative disorders might become possible.